2021
DOI: 10.31744/einstein_journal/2021ao5710
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of echocardiography and chest tomography for pulmonary hypertension screening in patients awaiting lung transplantation

Abstract: Objective: To examine the accuracy of a pulmonary hypertension screening strategy based on a combination of echocardiographic data and tomographic measurements (pulmonary artery diameter and pulmonary artery diameter to ascending aorta diameter ratio) in patients with chronic lung disease referred for lung transplantation. Methods: A retrospective observational study with patients with pulmonary emphysema or fibrosis referred for transplantation between 2012 and 2016. Pulmonary hypertension was defined as mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…According to the QUADAS-2 standard, all articles were included in case selection without case control and inappropriate exclusion. In the test and gold standard, Iyer et al ( 15 ), Shin et al ( 16 ), Degani-Costa et al ( 18 ), and Mohamed Hoesein et al ( 20 ) showed that the results were unknown, Shujaat et al ( 10 ) did not mention the interval between study CT and RHC, and the remaining studies were controlled within half a year. All twelve articles were Grade B or above (see Figures 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the QUADAS-2 standard, all articles were included in case selection without case control and inappropriate exclusion. In the test and gold standard, Iyer et al ( 15 ), Shin et al ( 16 ), Degani-Costa et al ( 18 ), and Mohamed Hoesein et al ( 20 ) showed that the results were unknown, Shujaat et al ( 10 ) did not mention the interval between study CT and RHC, and the remaining studies were controlled within half a year. All twelve articles were Grade B or above (see Figures 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%